Evaluation of rapid detection system for Escherichia coli in water samples - Pipitsombat, Chanikarn; Phasuk, Kanchana; Suwan, Supakorn; Piyawattanametha, Wibool (My University, 2017)
We demonstrated a fast detection platform for Escherichia coli (E. coli) in water. The system is based on a fluorescence detection technique by determining enzyme β-D-glucuronidase (GUD) activity and relating that activity to E. coli concentration. We found the portable E. coli detection platform is able to detect both the fluorescence 4-MU signal from the reaction of GUD assay from 0.01-1 μg/ml and to enumerate the number of E. coli in the range of 105-107 CFU/ml. The required incubation time is in between 20-240 min. In addition, we can estimate the maximum of incubation time for detecting minimum of E. coli 1 CFU/ml from the equation to be 576 mins. Our preliminary study demonstrates that the system can be used to enumerate the number of E. coli in water on-site and requires less detection time than traditional E. coli methods.
Keywords: b-D-glucuronidase (GUD); drinking water; Escherichia coli; fluorescence; portable detector